Best Practice Program Kewirausahaan Dalam Pendidikan Anak Usia Dini (Studi Multi Situs Tk Adni Islamic English School Surabaya Dan Tk Islam Bakti 4 Ypbwi Gresik) - Haq, Ahmad Matinul; Ariska, Anggi; Mukarromah, Siti Afifatul; Wijayanti, Dewie Tri; Khamidi, Amrozi (Universitas Negeri Malang, 2023)
Abstract: The importance of entrepreneurship education in early childhood is realized by the fact that early childhood is a period of growth and development that requires stimulation of everyday learning concepts. Introducing entrepreneurship to early childhood can influence children's views on entrepreneurship to develop positive attitudes towards entrepreneurship. This study aims to find out why schools implement entrepreneurship programs from an early age, and find out the practical forms of implementing programs in order to develop entrepreneurship programs, as well as find out the similarities and differences in the implementation of entrepreneurship programs in Kindergarten Adni Islamic English School Surabaya and Kindergarten Islam Bakti 4 YPBWI Gresik. The method used in this study uses descriptive qualitative research methods. Source of data in this study using purposive sampling. Data collection techniques using direct observation, interviews (formal and informal) and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of the study show that these two early childhood education institutions have carried out entrepreneurship education well. At the Adni Islamic English School Surabaya Kindergarten, the Entrepreneurship Program is Cooking Class, Shopping at the Market, Market Day, Field Trip, Sharing Activities, Infaq Activities, and Family Day, while the YPBWI Gresik Islamic Bakti 4 Kindergarten carries out a Life Skills Center, Visits to Markets, and Summits. Topic Celebration. Factors that encourage the implementation of entrepreneurship education are student enthusiasm, teacher creativity in preparing programs, and support from related parties. While the obstacles are related to facilities that are not always ready to support learning and external factors outside of entrepreneurial activities.Keywords: Entrepreneurship education; Early childhood; Entrepreneurial activityAbstrak: Pentingnya pendidikan kewirausahahaan pada anak usia dini disadari dengan kenyataan bahwa usia dini merupakan masa tumbuh kembang yang memerlukan stimulasi konsep-konsep pembelajaran sehari-hari. Memperkenalkan kewirausahaan bagi anak usia dini dapat memengaruhi pandangan anak-anak tentang kewirausahaan mengembangkan sikap positif terhadap kewirausahaan. penelitian ini bertujuan mengetahui mengapa sekolah menerapkan program kewirausahaan sejak usia dini, dan mengetahui bentuk praktik program penerapan yang dilakukan agar dapat mengembangkan program kewirausahaan, serta mengetahui persamaan dan perbedaan penerapan program kewirausahaan di TK Adni Islamic English School Surabaya dan TK Islam Bakti 4 YPBWI Gresik. Metode yang digunakan dalam penelitian ini menggunakan metode penelitian kualitatif deskriptif. Sumber data dalam penelitian ini menggunakan purposive sampling. Teknik pengumpulan data menggunakan observasi langsung, wawancara (formal dan informal) dan dokumentasi. Teknik analisis data yang digunakan adalah reduksi data, penyajian data ,dan penarikan kesimpulan. Hasil penelitian menunjukkan menunjukkan bahwa kedua lembaga pendidikan anak usia dini ini telah menjalankan pendidikan kewirausahaan dengan baik. Di TK Adni Islamic English School Surabaya melaksanakan program kewirausahaan Cooking Class, Belanja di Pasar, Market Day, Field Trip, Kegiatan Berbagi, Kegiatan infaq, dan Family Day sedangkan TK Islam Bakti 4 YPBWI Gresik melaksanakan Sentra Keterampilan Hidup, Berkunjung ke Pasar, dan Puncak Perayaan Topik. Faktor yang mendorong pelaksanaan pendidikan kewirausahaan adalah antusiasme siswa, kreativitas guru dalam menyusun program, dan dukungan dari pihak terkait. Sedangkan penghambatnya berkaitan dengan sarana yang tidak selalu siap untuk menunjang pembelajaran dan faktor eksternal di luar kegiatan kewirausahaan.Kata kunci: Pendidikan kewirausahaan; Anak usia dini; Kegiatan kewirausahaan